Crosstalk between mitochondrial biogenesis and mitophagy to maintain mitochondrial homeostasis - Liu, Lei; Li, Yanjun; Chen, Guo; Chen, Quan (Journal of biomedical science, 2023)
Mitochondrial mass and quality are tightly regulated by two essential and opposing mechanisms, mitochondrial biogenesis (mitobiogenesis) and mitophagy, in response to cellular energy needs and other cellular and environmental cues. Great strides have been made to uncover key regulators of these complex processes. Emerging evidence has shown that there exists a tight coordination between mitophagy and mitobiogenesis, and their defects may cause many human diseases. In this review, we will first summarize the recent advances made in the discovery of molecular regulations of mitobiogenesis and mitophagy and then focus on the mechanism and signaling pathways involved in the simultaneous regulation of mitobiogenesis and mitophagy in the response of tissue or cultured cells to energy needs, stress, or pathophysiological conditions. Further studies of the crosstalk of these two opposing processes at the molecular level will provide a better understanding of how the cell maintains optimal cellular fitness and function under physiological and pathophysiological conditions, which holds promise for fighting aging and aging-related diseases.